Involvement in Health Behavior After Heart Transplantation: The Role of Personal Resources and Health Status. Single-Center Observational Study - Mierzyńska, Anna; Kokoszka, Andrzej; Jerzak-Wodzyńska, Grażyna; Sobieszczańska-Małek, Małgorzata; Zieliński, Tomasz; Piotrowicz, Ryszard (Frontiers in Psychology, 2021)
Introduction. Heart transplantation affects all spheres of the patients’ functioning - their physical well-being and coping with everyday situations, as well as their identity and social functioning. Its long-term effects depend on the effective cooperation with the transplant team. Post-transplant patients are expected to be committed to adherence to recommendations. Patients' subjective characteristics could increase the risk of difficulties during treatment or might have a protective effect. The major aim of the study was to evaluate the level of engagement in health behavior in heart transplant recipients in relation to their personal resources, such as personality traits, and their health status. Material and method. The observational ex post facto model was proposed. Participants completed a set of psychological questionnaires. In the study there were used questionnaires regarding health behaviour (HBI), personality traits (NEO-FFI), health locus of control (MHLC), self-efficacy (GSES) and health status (GHQ-28). The group included in the analyses consisted of 107 heart transplant patients. They ranged in age from 19 to 75 years; 10.3% of them were women. Results. According to norms 71% patients reported high level of engagement in health behavior. There were significant differences in the level of dietary habits and other types of health behaviors. The best predictors of overall health behavior were conscientiousness (β=0.20, p<0.05) and health locus of control (Powerful Others) (β=0.25, p<0.05). The prophylaxis behavior was related significantly to the level of conscientiousness (p<0.05) and health locus of control (Internal and Powerful Others) (p<0.05; p<0.01). The level of positive mental attitude was related significantly to agreeableness ( p<0.05), health locus of control (Powerful Others) (p<0.01) and self-efficacy (p<0.01). Everyday healthy practices were related significantly to openness to experience (p<0.01) and health locus of control (all categories: Internal, Powerful Others and Chance) (p<0.05; p<0.01; p<0.05 respectively). Conclusions. Majority of heart transplant patients is engaged in high level of health behavior. Among the various forms of health-relevant habits, heart transplant patients adhere significantly less frequently to a healthy diet. Among examined resources, the best predictors of caring about health are health locus of control and level of conscientiousness according to Big Five concept.